2009
DOI: 10.1111/j.1365-2486.2009.01995.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale redistribution of maximum fisheries catch potential in the global ocean under climate change

Abstract: Previous projection of climate change impacts on global food supply focuses solely on production from terrestrial biomes, ignoring the large contribution of animal protein from marine capture fisheries. Here, we project changes in global catch potential for 1066 species of exploited marine fish and invertebrates from 2005 to 2055 under climate change scenarios. We show that climate change may lead to large-scale redistribution of global catch potential, with an average of 30-70% increase in high-latitude regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
728
1
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 1,018 publications
(764 citation statements)
references
References 34 publications
26
728
1
9
Order By: Relevance
“…Another critical point is whether ectothermic prey with a strict thermal optimum, such as myctophid fish [56], will be able to track the shift of the water masses to maintain their thermal optimum. In other parts of the world, several studies indicated that fish populations are responding to climate change by shifting their geographical distribution [4,57,58]. Unfortunately, myctophid fish are poorly studied in the sub-Antarctic waters and their response to future warming is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Another critical point is whether ectothermic prey with a strict thermal optimum, such as myctophid fish [56], will be able to track the shift of the water masses to maintain their thermal optimum. In other parts of the world, several studies indicated that fish populations are responding to climate change by shifting their geographical distribution [4,57,58]. Unfortunately, myctophid fish are poorly studied in the sub-Antarctic waters and their response to future warming is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Fish species distribution is projected to shift in the future, resulting in higher diversity and fisheries potential in higher latitudes (Cheung et al 2010). This will potentially result in food security and livelihood issues for countries located in the more tropical zones of the SCS.…”
Section: Threatsmentioning
confidence: 99%
“…Projections (A1B scenario) of global catch potential from 2005 to 2055 show an average of 30-70 % increase in high latitude regions and a~40 % decline in the tropics (Cheung et al 2010). Further modelling by Cheung et al (2011) projects that these fishery catch potentials may be reduced by an additional~10 % with the inclusion of biogeochemical factors (under the A1B scenario by 2050).…”
Section: Observed and Anticipated Impacts Of Climate Changementioning
confidence: 99%